LIMITA CREŞTERII DATORIILOR EXTERNE - Maximilian, Silvestru; Teleucă, Lina (CEP USM, 2007)
The debut of external crisis is the biggest deficiency in the way of state economic progress. The level of external debut does not only brake the possibility of some new investitional credits but conduct to the inacapacity to serve this debut.
Keywords: datorii externe